New constraints on methane fluxes and rates of anaerobic methane oxidation in a Gulf of Mexico brine pool via in situ mass spectrometry - Wankel, S D; Joye, S B; Samarkin, V A; Shah, S R; Friederich, G; Melas-Kyriazi, J; Girguis, P R (Deep-Sea Research. Part II: Topical Studies in Oceanography, 2010)
Deep-sea biogeochemical cycles are, in general, poorly understood owing to the difficulties of making measurements in situ, recovering samples with minimal perturbation, and, in many cases, coping with high spatial and temporal heterogeneity. In particular, biogeochemical fluxes of volatiles such as methane remain largely unconstrained because of the difficulties with accurate quantification in situ and the patchiness of point sources such as seeps and brine pools. To better constrain biogeochemical fluxes and cycling, we have developed a deep-sea in situ mass spectrometer (ISMS) to enable high-resolution quantification of volatiles in situ. Here we report direct measurements of methane concentrations made in a Gulf of Mexico brine pool located at a depth of over 2300 m. Concentrations of up to 33 mM methane were observed within the brine pool, whereas concentrations in the water directly above were three orders of magnitude lower. These direct measurements enabled us to make the first accurate estimates of the diffusive flux from a brine pool, calculated to be 1.1±0.2 mol m−2 yr−1. Integrated rate measurements of aerobic methane oxidation in the water column overlying the brine pool were ∼320 $μ$mol m−2 yr−1, accounting at most for just 0.03{%} of the diffusive methane flux from the brine pool. Calculated rates of anaerobic methane oxidation were 600–1200 $μ$M yr−1, one to two orders of magnitude higher than previously published values of AOM in anoxic fluids. These findings suggest that brine pools are enormous point sources of methane in the deep sea, and may, in aggregate, have a pronounced impact on the global marine methane cycle.
Keywords: HOV Alvin (Human Occupied Vehicle); ROV Jason (Remotely Operated Vehicle)